2016
DOI: 10.1007/s12016-016-8594-z
|View full text |Cite
|
Sign up to set email alerts
|

Gorham-Stout Disease: a Clinical Case Report and Immunological Mechanisms in Bone Erosion

Abstract: Gorham-Stout disease (GSD) is a rare condition of osteolysis with excessive lymphangiogenesis within bone tissue. The etiology of this condition remains unknown but seems to affect mainly children and young adults of both genders all over the world. Unfortunately, there is no standardized method for diagnosis; however, histopathology remains as the gold standard. This condition is often misdiagnosed due to its varying clinical presentations from case-to-case. Here, we report the case of an 8-year-old girl who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…After CES had yielded negative results, we performed aCGH, which provided no relevant findings. Ultimately, the patient was diagnosed with Gorham-Stout Disease (GSD), a rare disorder characterized by angiogenesis, lymphangiomatosis, and severe bone resorption (106). The exact cause of GSD is unknown and no environmental, immunological or genetic risk factors have been identified.…”
Section: Resultsmentioning
confidence: 99%
“…After CES had yielded negative results, we performed aCGH, which provided no relevant findings. Ultimately, the patient was diagnosed with Gorham-Stout Disease (GSD), a rare disorder characterized by angiogenesis, lymphangiomatosis, and severe bone resorption (106). The exact cause of GSD is unknown and no environmental, immunological or genetic risk factors have been identified.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that activation of the osteoclastogenic process is induced by immune mechanisms in affected bone tissue because the number of osteoclasts increases in the GSD lesion. 31 Alternatively, osteolysis could be caused by the abnormal proliferation of lymphatic vessels compressing bone. Moreover, the activity of osteoclasts is influenced by some cytokines that are secreted by the lymphatic endothelial cells.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…As it is known that GSD osteolysis occurs adjacent to local proliferation of lymphatic vessels, the activation of osteoclasts and lymphangiogenesis is essential for the progress of GSD [21]; lymph is frequently seen in the osteolytic lesions. Franco-Barrera et al [22] reported that the activation of the osteoclastogenic process that affects bone tissue is induced by immune mechanisms.…”
Section: Discussionmentioning
confidence: 99%